Окриленість словом: науковий універсум Степана Хороба - Мафтин, Н.В. (Слово і Час, 2019)
У статті охарактеризовано творчу індивідуальність Степана Хороба; висвітлюється його внесок у розвиток українського літературознавства ХХ – ХХІ ст. Також простежено шлях його становлення як журналіста, театрального оглядача, історика й теоретика літератури, висвітлено діяльність ученого як педагога вищої школи, як журналіста й перекладача з білоруської мови. Науковий доробок ученого розглянуто в аспекті компаративних досліджень, теорії та історії драми. The paper characterizes Stepan Khorob’s creative individuality and highlights his contribution into the development of Ukrainian literary studies of the 20th – 21st centuries. It also traces his way of formation as a journalist, theatrical reviewer, historian of literature and critic, as well as the scholar’s activity as a University lecturer. The dominants of his scholarly and critical works are defined as universality of philosophical thinking, academic fundamentality, analytical approach to the comprehension of a fictional text that leads to the profound understanding of life in general. A special attention is paid to the scholar’s interest in the genre of drama (in particular religious drama and Ivan Franko’s plays). The methodological basis for Stepan Khorob’s research studies is the national existential dominant, attention to the European literary and scholarly heritage. In the rich spectrum of his scholarly interests one can recognize a humanistic tradition of Ukrainian literary studies inherited from Ivan Franko. A special respect for the cultural legacy encouraged the scholar to focus on the works by Western Ukrainian playwrights of the 1920s–1930s, withdrawn from the history of Ukrainian culture by the occupant’s censorship of the time. The paper also mentions Stepan Khorob’s work on publication of the works by Volodymyr Derzhavyn, Leonid Biletskyi, Leonid Rudnytskyi and popularization of these diaspora scholars’ names and research works among students. In addition, it outlines achievements of Stepan Khorob as a translator from the Belarusian language.